Imaging analytical technique to assess gastrointestinal motility in vivo using zebrafish larvae with diabetes mellitus-like traits. - Jessica C M Hui; Peng Du; Sarah E Webb; Julia Y H Liu; Man Piu Ngan; Zengbing Lu; Heidi S H Ng; Lingqing Yang; Aleena Khalid; Luping Liu; Zitong Li; Yingyi Deng; et al. (PLoS ONE, 2024)
In diabetes mellitus (DM), the prevalence of gastrointestinal (GI) complications, including constipation, diarrhoea, gastroparesis, and/or enteropathy, can be up to ~75%. In this study, we compared three zebrafish larvae models of DM and established an analytical protocol for GI motility. Larvae were fed with either a standard diet (SD; control), or one of three diets to induce a DM-like phenotype: excessive feeding of SD food (ED), a high-fat diet (HFD), or exposing SD-fed larvae to 30 mmol/L glucose (SDG). DM was confirmed using a body-mass index, assessment of adipose deposit areas, two glucose assays, and one insulin assay. An analytical technique, whereby GI motility was quantified using pixel differences to track displacement along the centreline of the anterior, middle, and posterior intestine (AI, MI, and PI, respectively), was developed. Our results indicated that clear DM-like traits were observed in the HFD and SGD models, but not the ED model. In the SD controls, the AI showed similar anterograde and retrograde contractions indicating normal GI mixing; the MI exhibited more prominent forward contractions, and the PI showed distinct rectal waves. Compared to the SD, the HFD and SDG models exhibited significantly increased and decreased contraction velocities and could be used as models of diarrhoea and constipation in DM, respectively, while the ED model showed comparatively little change in motility. Together, these data indicate that complex changes in GI motility are associated with diet and therapeutics used to alleviate GI complications in DM should take these into account. Ultimately, the HFD and SDG models can be used to investigate different aspects of GI motility in association to DM. Hence, zebrafish are a useful model for studying GI dysfunctions due to DM and/or DM medication side-effects.